THE EFFECT OF COLLABORATIVE WRITING TOWARDS STUDENTS’ WRITING SKILL AT TENTH GRADE OF SMAN 10 TANGERANG IN ACADEMIC YEAR 2020/2021 - Adinsyah, Divi; Nirmala, Nirna (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2020)
ABSTRACTThe aim of this research was to know whether there is a significant effect of collaborative writing strategy at the tenth grade of SMAN 10 Tangerang. This research is quasi-experiment and was conducted by using a quantitative method, with 35 students as the sample which taken non-random by using purposive sampling. The Population was students at the tenth grade of SMAN 10 Tangerang. The hypothesis data was tested using the formula of Wilcoxon Sign Rank. The result of the study showed that effect of collaborative writing gave positive significant effect towards students’ writing skill. The reaction of students towards collaborative writing showed a significant result. Their score increased because of students learnt how to produce a genre text (recount text) with their peers who had a score which is above the minimum criteria. Students who had a score below minimum criteria. got guidance from their peers who had score above minimum criteria. Moreover, students had pre-test scores which are below minimum criteria, got increased score of post-tests after getting guidance by their peers. In summary, there was an improvement in students’ writing skill after the implementation of learning how to produce text by using collaborative writing.Keywords: Writing Skill, Collaborative Writing.